2018
DOI: 10.1192/bjb.2017.30
|View full text |Cite
|
Sign up to set email alerts
|

Pathways to Recovery: development and evaluation of a cognitive–behavioural therapy in-patient treatment programme for adults with anorexia nervosa

Abstract: Aims and methodA cognitive–behavioural therapy in-patient treatment model for adults with severe anorexia nervosa was developed and evaluated, and outcomes were compared with the previous treatment model and other published outcomes from similar settings.ResultsThis study showed the Pathways to Recovery outcomes were positive in terms of improvements in body mass index and psychopathology.Clinical implicationsAdults with anorexia nervosa can achieve good outcomes despite longer illness duration and comorbiditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Length of stay ranged from 32 to 182 days, with most programmes offering treatment for 10-16 weeks, and a recent metaanalytic review found a mean length of stay of 86.3 days [13]. For inpatient treatment, 15 adult inpatient cohorts (n = 2100) from different countries (USA/Canada, Australia/New Zealand, Germany, Italy, UK) reported mean admission BMIs ranging from 13.9 to 16.3 kg/m 2 [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] and a meta-analysis reported a mean length of stay of 105.6 days across Europe and 49.1 days across USA [13]. A recent audit from the Quality Network for Eating Disorders in the UK, which included data submitted from all adult inpatient eating disorder services in England (n = 30) and two in Scotland (out of four adult inpatient eating disorder services), reported the mean length of stay for inpatient treatment as 116 days [43].…”
Section: Introductionmentioning
confidence: 99%
“…Length of stay ranged from 32 to 182 days, with most programmes offering treatment for 10-16 weeks, and a recent metaanalytic review found a mean length of stay of 86.3 days [13]. For inpatient treatment, 15 adult inpatient cohorts (n = 2100) from different countries (USA/Canada, Australia/New Zealand, Germany, Italy, UK) reported mean admission BMIs ranging from 13.9 to 16.3 kg/m 2 [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] and a meta-analysis reported a mean length of stay of 105.6 days across Europe and 49.1 days across USA [13]. A recent audit from the Quality Network for Eating Disorders in the UK, which included data submitted from all adult inpatient eating disorder services in England (n = 30) and two in Scotland (out of four adult inpatient eating disorder services), reported the mean length of stay for inpatient treatment as 116 days [43].…”
Section: Introductionmentioning
confidence: 99%